The influence of school principals’ digital leadership on teachers’ competency in integrating artificial intelligence: a systematic thematic review - Zeng, Meiyu; Cheah, Kenny S. L.; Abdullah, Zuraidah (Frontiers in Education, 2025)
This systematic thematic review aimed to examine how the digital leadership of principals affects teachers’ capacity to use artificial intelligence technology in their teaching. In this study, the Unified Theory of Acceptance and Use of Technology (UTAUT) is combined with transformational leadership theory to provide an analytical framework. Fourteen empirical papers published between 2021 and 2025 were identified from the Scopus, Web of Science, and ERIC databases following the PRISMA guidelines. By allocating resources, providing support for professional development, creating learning communities, and cultivating a positive culture, principals may significantly influence teachers’ acceptance and use of AI technology. In addition to improving teachers’ perceptions of the value and usability of AI technologies, effective leadership also greatly increase their technological self-efficacy and help them better integrate it. Key facilitators like the complementarity of dual leadership, incentives, and continuing professional development are identified in the study, even if AI integration still faces obstacles, including inadequate infrastructure, teacher reluctance to use AI, and a lack of organizational support. This research presents a theoretical integrative viewpoint for comprehending the acceptance of educational technology. It also offers theoretical justification and useful recommendations for leadership development, educational reform, and enhancing teachers’ AI skills. It highlights the need for leadership in advancing AI integration and educational fairness in the context of the digital revolution of education.